Millimeter Wave Fuze Radome Design Based Bandpass Frequency Selective Surface - Min Zhao; Junjian Bi; Juan Xu; Jianping Zhao (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper studies a fuze radome system applied to millimeter waves. The system consists of feed antenna, radome, planar FSS array or curve conformal array. Microstrip antenna is used as the feed antenna. Based on the principle of equispaced and equal period respectively, cross units loading single layer dielectric form planar and curve FSS array. The FSS radome system can improve the permeability of hood to electromagnetic waves (EM) of passband, and reduce the interference of complex EM in the external environment to the system. The FSS radome will not deteriorate radiation characteristics of the feed antenna. The planar FSS radome has a passband of 98.2 GHz to 101.55 GHz with -10dB relative bandwidth of 3.35%. The curve FSS radome has a passband of 96.3 GHz to 101.8 GHz with -10dB relative bandwidth of 5.5%. In addition, the radiation characteristics of the proposed system are analyzed. It is found that the radiation pattern of the antenna is basically consistency before and after loading the radome.